Oncogenes and tumor-suppressor genes in mesothelioma--a synopsis. - Lechner, J F (1997)
Invariably mesothelioma is diagnosed late in the development of the disease when treatment is no longer effective. Therefore, a key to reducing the mortality rate of this neoplasm is knowledge of the general sequence of genetic events between initiation of mesothelial cells and the emergence of the metastatic tumor cells. Unfortunately, relatively little is known about the early changes in the genesis of this disease. Of the known changes, the most frequent are in the tumor-suppressor genes p16INK4a and NF2 and possibly the SV40 virus large T-antigen oncogene. The molecular nature of the changes in these genes as well as other alterations are addressed in this overview.